Implications of CEO Succession Origin and In-House Experience for Audit Pricing. (January 2022) - Brockman, Paul; Krishnan, Gopal; Lee, Hye Seung (Grace); Salas, Jesus M.
Prior research indicates that the CEO has a significant impact on financial reporting decisions. However, there is limited research on the implications of CEO succession origin (hiring a CEO from the inside as opposed to from the outside) for auditors. We find that on average, audit fees are greater by about 8% when a CEO is hired from the outside than when a CEO is promoted from within. We also find that the CEO's in-house experience (the number of years the CEO has worked in the firm before becoming the CEO) is negatively associated with audit fees, suggesting that the CEO's in-house experience enhances the CEO's competence in understanding how the firm's performance should map into the financial statements, resulting in lower audit risk. Finally, our findings suggest that the CEO's in-house experience plays an important role in mitigating audit risk in firms with poor corporate governance quality.